Management of Cellphone Use to Improve Learning Concentration at Sirojul Waalidain Islamic Boarding School - Taufik, Ilham; Ahmadiah , Didih; Tabroni, Imam; Oscar , Scherschligt; Jiao , Deng (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background Increasingly sophisticated technology has had an impact on pesantren, thus affecting the learning patterns of each student. Purpose. Due to the needs of schools that demand to use cellphones, namely madrasah aliyah, high school, and college levels. So the pesantren makes regulations both written and unwritten to regulate the ethical values of students. Method. With these regulations, there are many restrictions on the use of cellphones for students. Many problems arise in the use of cellphones, one of which is the concentration of learning for students. Results. In this study, the authors examined the management of the use of mobile phones to improve learning concentration at Pondok Pesantren Sirojul Waalidain. This study aims to determine how the pesantren's policy on the use of cellphones, why students are not disciplined in using cellphones, and what solutions are carried out by the pesantren to improve learning concentration. Conclusion. The method used in this research is a qualitative method with a case study approach. The types of data in this study can be divided into two, namely primary data and secondary data. The data collection techniques used are interviews, observation and documentation.